Чингис хааны хэн хэдийд, хэрхэн үнэлж ирсэн тухай - Жамбалсүрэн, Цэен-Норов (Historia Mongolarum, 2003)
Historians, scholars, politicians from medieval times evaluate differently the role of Chinggis khaan. The author makes a review of the evaluation of the role of Chinggis Khaan in the twentieth century and an impact of his ideology on it.